The colour betrays the poison - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Over 2500 plants punish their predators by producing poison when they are eaten by catalysing cyanogenic glycosides. The best known is cassava. Analysing and determining the levels of toxicity in plants is often constrained by a lack of required...